ANALISIS PENENTUAN HARGA ASET PADA PASAR MODAL ASIA PASIFIK: LOKAL ATAU GLOBAL - Sukasmanto (UGM, 2004)
The purpose ofthis study are to identify the empirical evidence whether the pricing error form using domestic CAPM when the use of global CAMP is appropriate, whether the security risk that is diversifiable domestically is also diversifiable globally and whether the use of domestic CAPM result in the same expected return as the use of global CAPM